Civil Islam atau Uncivil State: Masalah Demokratisasi dalam Masyarakat Muslim - Mujani, Saiful (Studia Islamika, 2001)
Hefner, in his book entitled Civil Islam, proposes Indonesia as a relevant case in the debate among students of Muslim society and democracy as to whether Islam is inimical to democracy. He argues that Indonesian Muslims are more likely to support a democratic political system because civil Islam, that is a set of beliefs within the Muslim community that supports the separation of religious and political authority, pluralism and tolerance of fellow (non-Muslim) citizens and their beliefs, is persistent. From a political culture approach to democracy, this culture is crucial for the emergence and consolidation of democracy. This book overstates the significance of civil Islam in the case of Indonesia, and cannot explain the fact that democracy is a rare phenomenon in the Muslim world, including in Indonesian history.DOI: 10.15408/sdi.v8i2.692